Living Qur’an; Implementasi Pengamalan Ayat-ayat Menyantuni Anak Yatim Masjid Paripurna - Fatah, Nasrul; Laili, Syarifah; Ismail, Hidayatullah (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2023)
Living Qur'an is a study carried out with a sociological phenomenological approach to the practice of community life based on Qur'anic values. This study aims to photograph how the values of the Qur'an is brought to life in the community of the Al-Washliyah mosque in Pekanbaru. The focus of the study in this study is on the implementation of Orphan compensation in these locations. This study is a field study using qualitative data collected by observation, interview and documentation techniques. The results of this study indicate that the implementation of compensation to orphans in the Al-Washliyah mosque in Pekanbaru city is realized in the form of programmed compensation with attention to basic needs and sustainability. Compensation is given not only in the form of consumptive material but also in the form of spiritual guidance.